Diesel combustion of oil and refrigerant mixture during pump-down of air conditioners. (March 2017) - Higashi, Tomohiro; Saitoh, Shizuo; Dang, Chaobin; Hihara, Eiji
Highlights: Compressor destruction accidents during pump-down were experimentally investigated. Mixture of refrigerant, air and lubricating oil was adiabatically compressed. It was revealed that the accidents are caused by diesel combustion of mixture. Even non-flammable refrigerants could burn in the compressor. The oil was necessary for burning, however, the refrigerant led intense combustion. Abstract: Compressor-destruction accidents during the pump-down operation of air conditioners were experimentally investigated. Assuming air penetration into refrigerant tubes, the gaseous mixture of the air, refrigerant, and lubricating oil for a compressor was compressed by the compressor with different refrigerant concentrations, and the diesel combustion of the mixture was examined. The compressor was simulated by a small-scale engine. R1234yf, R32, R410A, R134a, R22, and R125 were tested as refrigerants. The mixture burned via adiabatic compression when the refrigerant concentration was low, which means that accidents during the pump-down were caused by the diesel combustion of the mixture. The refrigerant burned and caused intense pressure increase. The mixture without the oil did not burn under any refrigerant concentration, which suggests that oil is necessary for the combustion. These phenomena were observed in the results for R1234yf, R32, R410A, R134a, and R22. Thus, combustion was observed under certain conditions even for refrigerants categorized as non-flammable.